Boundedness for multilinear Marcinkiewicz operators on certain Hardy spaces - Liu Lanzhe (International Journal of Mathematics and Mathematical Sciences)
The boundedness for the multilinear Marcinkiewicz operators on certain Hardy and Herz-Hardy spaces are obtained.